Comparison of the effects of treatment of peri-implant infection in animal and human studies: systematic review and meta-analysis - Faggion Junior, Clóvis Mariano; Chambrone, Leandro; Gondim, Valéria; Schmitter, Marc; Tu, Yu-Kang (Clinical oral implants research, 2010)
Objective: The main objective of this systematic review is to compare the effects of treatment of peri-implant infection between animal and human studies. Material and methods: A literature search was conducted using the Medline, Cochrane Central Register of Controlled Trials, and Latin American and Caribbean Health Sciences Literature databases up to and including May 2008. In addition, bibliographies of systematic reviews on peri-implant diseases were searched manually. Non-surgical and surgical treatments of peri-implantitis/mucositis in animal models or human studies were compared. Meta-analysis was conducted to investigate the difference between the reported treatment effects in animal and human studies. Changes in probing pocket depth (PPD) and probing attachment level (PAL) from baseline measurements were used as measures of outcome. Single-level and multilevel meta-regression analysis was performed by taking into account the different follow-up times of the studies included. Results: The single-level and multilevel random-effects meta-analysis showed that the difference in PPD reduction [0.31 mm, 95% confidence interval (CI): −0.27, 0.88] and in PAL gain (0.21 mm, 95% CI: −0.47, 0.88) between animal and human studies was not statistically significant. The random-effects meta-regression suggested that studies with longer follow-up times revealed greater PPD reduction (0.25 mm per month, 95% CI: 0.14, 0.35). However, when the different follow-up times were taken into account, these differences became greater. Substantial heterogeneity between studies was found in the meta-analyses (I2=97.6% for animal studies and 99.9% for human studies). Conclusion: There was great heterogeneity between human and animal studies in terms of study designs and treatment procedures. Therefore, the results from this meta-analysis should be interpreted with caution. Heterogeneity between studies and its causes merit further investigations. To cite this article: Faggion CM Jr, Chambrone L, Gondim V, Schmitter M, Tu Y-K. Comparison of the effects of treatment of peri-implant infection in animal and human studies: systematic review and meta-analysis. Clin. Oral Impl. Res. 21, 2010; 137-147. doi: 10.1111/j.1600-0501.2009.01753.x
Gesehen am 07.02.2023